The Comparison of Temporary Crown Retention Among Three Temporary Cements - Arwatchanakan, Sukontip; Phatomworachad, Schwinn; Kosuwon, Prow; Phetpanomporn, Sirintana; Luansritisakul, Punyanuch (Khon Kaen University Dental Journal, 2018)
Temporary cements are crucial for retaining temporary crowns in fixed dental prosthesis. The aim of this study was to compare the temporary crown retention among three temporary cements and to evaluate the mode of failure of temporary crowns, which fabricated with self-cured acrylic (Dentalon Plus, Heraeus Kulzer GmbH, Germany) when cemented with zinc oxide eugenol cement (Temp bond, Kerr, USA), zinc oxide non-eugenol cement (Temp Bond NE, Kerr, USA) and resin temporary cement (Temp Bond Clear with Triclosan, Kerr, USA). Sixty maxillary first premolars were prepared for full temporary crown restorations. The nails were fixed on the occlusal surface by applying cyanoacrylate glue, then the specimens were tested for retention by using tensile mode of the universal testing machine (LR 30K, LLOYD Instruments, UK) at crosshead speed of 0.5 mm/min. All temporary crowns were luted with temporary cements under fingers pressure for 5 seconds then kept the specimens in position under 5-kg load using the universal testing machine for 5 minutes. All specimens were stored in distilled water at 36๐C in water bath for 24 hours. After that, all specimens were investigated for bond strength by using tensile mode of the universal testing machine at crosshead speed of 0.5 mm/min. After the removal of the temporary crowns, failure modes were observed. The median retention of zinc oxide eugenol cement group was 324.35 (minimum 52.52, maximum 553.20) kPa, zinc oxide non-eugenol cement group was 222.43 (minimum 20.00, maximum 439.56) kPa and resin temporary cement group 117.10 (minimum 24.94, maximum 349.13) kPa. When using Kruskal-Wallis test and Mann-Whitney U test, no statistically significant difference was found between zinc oxide eugenol group and zinc oxide non-eugenol cement group (p = 0.058) but resin temporary cement group was found to be significantly different from both zinc oxide eugenol group and zinc oxide non-eugenol cement group (p < 0.001 and 0.01, respectively). Most of specimens from three groups were found with the failure mode type three, which is most of the temporary cement (3/4) adhere to the internal surface of the temporary crown.